Perancangan Turbin Tife Pelton Untuk Miniatur Pembangkit Listrik Tenaga Mikro Hidro - Wan Azlan Abdullah (Universitas Batanghari Jambi, 2019)
The highest axle rotation is found in the use of variation comparison differences: The 4-to-1 gear comparison difference which results in a round axle of: 420 and 400 rpm. While the lowest axle rotation occurs peda different variations of gear comparison of 280 rpm. The water discharge that rotates the Pelton turbine generates a generator output voltage of 13.15.18 volts. Power generated power can be battery Mecharger 12 Volts 7.0 Ah and can be in the lamp burden 24 watts. As for the advice in the design of laboratory scale testing equipment of Pelton scales as follows; If you want to increase the voltage capacity of the resulting turbine so we have to enlarge the diameter of the turbine then increase the water discharge and increase the gear rotation ratio so that the generator output power is greater.